Associated Complication of Gastrointestinal Stromal Tumours of the Small Intestine - Nikolay A. Trifanov; Alexander Ya. Korovin; Alexander N. Manzhos; Alexey V. Barsuk (Кубанский научный медицинский вестник)
Aim. To consider the possibility of the diagnosis of a rare small bowel tumour complicated by small bowel obstruction and small bowel bleeding, as well as the surgical treatment of this pathology using a minimally invasive surgical approach.Results and discussion. The authors present a clinical case of associated complication of a gastrointestinal stromal tumour (GIST) of the small intestine in a 48-year-old patient. The patient was admitted to a surgical clinic with small bowel obstruction, episodes of intestinal bleeding and anaemia. The diagnosis was determined using CT enterography. In line with the current trends for minimally invasive surgery, minimally invasive laparotomy was performed drawing on the CT mapping of the anterior abdominal wall. The last stage involved in the morphological verification of GIST, which employs a standard procedure of IHC testing, revealed a malignant GIST, spindle cell variant. The verified histotype of a small intestinal tumour provides the opportunity to choose the necessary variant of adjuvant chemotherapy, as well as to improve general and relapse-free survival.Conclusion. Minimally invasive operations can be performed in the complicated course of GIST due to the biological properties of this pathology (absence of lymphogenic metastasis and infiltrative growth) without decreasing five-year survival rate. The use of CT helps make a topical diagnosis and plan minimally invasive surgical treatment.